2020
DOI: 10.1111/ijpo.12658
|View full text |Cite
|
Sign up to set email alerts
|

Adversity exposure and obesogenic food consumption in young children: The transgenerational role of emotion dysregulation

Abstract: Background: Childhood adversity is linked with unhealthy eating behaviours and obesity, but the mechanisms underlying this association are unclear, specifically the transgenerational behavioural precursors that develop in early childhood. Objective: To determine whether adversity predicts change in obesogenic food consumption through child emotion dysregulation, and whether caregiver emotion dysregulation modifies this association. Methods: Participants included 190 low-income caregiver-child dyads (mean child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…47 In support of this notion, a recent study found that poor emotion regulation explained the link between childhood adversity and obesogenic food consumption in low-income children. 48 Studies that assess FI-related stress in children and emotional overeating are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In support of this notion, a recent study found that poor emotion regulation explained the link between childhood adversity and obesogenic food consumption in low-income children. 48 Studies that assess FI-related stress in children and emotional overeating are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative work with low‐income women has shed light on how the use of food as a coping mechanism in response to food deprivation in childhood can persist into adulthood, 4 and a link between emotion dys‐regulation and emotional eating has been suggested 47 . In support of this notion, a recent study found that poor emotion regulation explained the link between childhood adversity and obesogenic food consumption in low‐income children 48 . Studies that assess FI‐related stress in children and emotional overeating are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…From the affections involved in feeding and being fed to the formation of eating habits that endure throughout one's life. Accepting or denying them are part of how, why, and what we deal with our family and their stories that constitute us (Erriu et al, 2020;Huffhines et al, 2020;Leung et al, 2019;Wagner, 2005).…”
Section: Chapter 117mentioning
confidence: 99%
“…In the field of clinical research, the self-regulation variable has appeared to be important for the explanation of other psychological constructs, such as personality ( Inzlicht et al, 2021 ), resilience ( de la Fuente et al, 2017 ), personal strengths ( Lerner et al, 2021 ), coping strategies ( Amate-Romera and de la Fuente, 2021 ), emotionality ( Lajoie et al, 2021 ) and perfectionism ( Thakre and Sebastian, 2021 ). Recently, studies have considered the dysfunctional level of self-regulation ( dys-regulation ) as a transdiagnostic variable ( p factor ) underlying numerous psychiatric psychopathologies ( Duncan et al, 1996 ; Choi and Abbott, 2020 ; Huffhines et al, 2020 ; Smith et al, 2020 ; Levin-Aspenson et al, 2021 ; Romer et al, 2021 ) varying levels of which are relevant to criminal pathologies ( Billen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%